Pengembangan Homestay Manggis untuk Mendukung Desa Wisata Angsana, Desa Setu, Kecamatan Jasinga, Kabupaten Bogor - Daniel Jehovah; Budi Setiawan; Brandon Fandra; Benjiro Lepar; Darren Owen (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
The development of homestays in Angsana Tourism Village, Setu Village, Jasinga District, Bogor Regency, is a strategic initiative aimed at supporting community-based tourism with a focus on enhancing the quality of services and homestay facilities. This program aims to strengthen the appeal of the tourist destination by improving the comfort of accommodations offered to visitors, while also empowering the local community by increasing economic welfare. The methods used in this program include field observations, intensive dialogue with homestay owners, and the implementation of a work program that involves improving the physical infrastructure of homestays, such as room cleaning, installing mosquito nets, ceiling repairs, curtain installation, and rearranging furniture. Additionally, homestay management training and the introduction of digital marketing strategies were provided to expand promotional reach and attract more tourists. The results of this program show a significant improvement in the comfort and aesthetics of the homestays, positively impacting the visitor experience. Thus, this program is expected to support sustainable tourism development in Angsana Tourism Village while enhancing the welfare of the local community through increased tourist visits.